Processing English Compounds in the First and Second Language: The Influence of the Middle Morpheme - Murphy, V; Hayes, J (2010)
Native English speakers tend to exclude regular plural inflection when producing English noun-noun compounds (e.g., rat-eater not rats-eater) while allowing irregular plural inflection within compounds (e.g., mice-eater) (Clahsen, 1995; Gordon, 1985; Hayes, Smith and Murphy, 2005; Lardiere, 1995; Murphy, 2000). Exposure to the input alone has been considered insufficient to explain this dissociation between regular and irregular plurals in compounds because naturally occurring compounds in English rarely have plurals of any type included within them (e.g., Gordon, 1985). However, the constraint on the production of plural inflection in English compounds could be derived from the patterns in which regular plural and possessive morphemes occur in the input. To explore this idea, native adult English speakers and adult Chinese learners of English were asked to process a series of compounds containing different medial morphemes and phonemes. Comparisons were made across compounds with regular and irregular plurals and possessive [-s]. Native speakers (NS) of English processed compounds with medial possessive morphology faster than compounds with medial regular plural morphology. The second language learners did not show the same pattern as the NSs, which could be due to the fact that they had considerably less exposure to the relevant input patterns relative to the NSs. Regular plurals may be excluded before a rightmost noun in English because the pattern " Noun-[-s] morpheme-Noun" is more frequently used for marking possession in English. Irregular plurals do not end in the [-s] morpheme and therefore do not " compete" with the possessive marker and, consequently, may be optionally included in compounds. It is possible, therefore, that the input English learners receive could indeed be sufficient to constrain this aspect of English compound production. © 2010 Language Learning Research Club, University of Michigan.